Penggunaan Media Film Dalam Penguasaan Kosakata Bahasa Jerman - Muhammad Nizam; Wahyu Kurniati Asri; Laelah Azizah (Phonologie : Journal of Language and Literature, 2021)
Abstract. This research was conducted to obtain data and information regarding students' mastery of German vocabulary using film media. This research is an experimental study using a German vocabulary mastery test. Data were analyzed by t-test. The population of this study were students of SMA Negeri 11 Makassar which consisted of 3 classes. The sample used is a random sample (Random Sampling). The number of samples is 2 classes, namely class XI IPS 1 which consists of 16 students as the experimental class and class XI IPS 3 which consists of 16 students as the control class. The results of the analysis show that the t value is 2.93 > t table 2.04227. The results of this study indicate that film media is effective in mastering German vocabulary at SMA Negeri 11 Makassar.